Komunikasi Publik Pemerintah dalam Penanganan Bencana Sumatera Utara: Studi Kasus Pemberitaan Media Online Kompas.com - Anisa Rambe; Ahmad Tamrin Sikumbang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the high risk of disasters in North Sumatra and the importance of effective government public communication in crisis situations, particularly through online media. This study aims to analyze how government public communication messages are represented and framed in Kompas.com news coverage related to disaster management. The method used is a qualitative approach with a case study design and qualitative content analysis. The data consists of Kompas.com news articles from the end of November to December 2025, selected purposively based on thematic relevance. The analysis was conducted through the stages of data collection, coding, interpretation of meaning, and drawing conclusions using framing theory. The results show that the media tends to frame disasters as emergencies with the main cause being natural factors, and presents the government as the main actor that is responsive through evacuation, aid distribution, and direct visits to disaster sites. Furthermore, there is a tendency for framing to build a positive image of the government, although in some cases criticisms regarding environmental aspects and policies have emerged. The conclusion of this study indicates that media framing plays a significant role in shaping public perception of government communication, thus requiring synergy between the government and the media to produce accurate, balanced, and reliable information in disaster situations.